PENINGKATAN KINERJA GURU DALAM MENDESAIN PEMBELAJARAN SECARA SISTEMATIS MELALUI SUPERVISI AKADEMIK PENGAWAS SEBAGAI UPAYA PENINGKATAN CAPAIAN MUTU PENDIDIKAN DI TAMAN KANAK-KANAK BINAAN KOTA BENGKULU TAHUN PELAJARAN 2013-2014 - Huzaipah Huzaipah (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2016)
An educator/teacher wherever He or She served to educate and teach, in charge of presenting his or her knowledge to learners, in order to transferring the knowledge it certainly requires experience, knowledge of who the learners, as well as how to convey that knowledge well. He needs to explore competency gives stock to him to draw up strategies, techniques, models and methods to present a topic or theme becomes more attractive, organized and integrated with competence contained in the material. It is an integral part of the Teaching Performance a teacher for all levels of education. The purpose of School Action Research is to determine the extent of the coaching supervisors in improving the performance of teachers in designing learning systematically through the regulatory supervision. School Action Research was conducted in three cycles, the results of action taken proven to improve the competence of teachers to achieve the ideal standard. In the first cycle of the 10 teachers that existed at the time of this research, the average value reached 68% increased to 72.5% and in the third cycle increased to 83%. The result of this action research indicates that coaching through academic supervision supervisors can improve the performance of teachers in designing learning systematically in kindergarten Patronage Bengkulu City reached 100% completeness.